Competition and relational contracts: the role of unemployment as a disciplinary device - Martin Brown; Armin Falk; Ernst Fehr (Institute for the Study of Labor (IZA), 2008)
When unemployment prevails, relations with a particular firm are valuable for workers. As a consequence, a worker may adhere to an implicit agreement to provide high effort, even when performance is not third-party enforceable. But can implicit agreements - or relational contracts - also motivate high worker performance when the labor market is tight? We examine this question by implementing an experimental market in which there is an excess demand for labor and the performance of workers is not third-party enforceable. We show that relational contracts emerge in which firms reward performing workers with wages that exceed the going market rate. This motivates workers to provide high effort, even though they could shirk and switch firms. Our results thus suggest that unemployment is not a necessary device to motivate workers. We also discuss how market conditions affect relational contracting by comparing identical labor markets with excess supply and excess demand for labor. Long-term relationships turn out to be less frequent when there is excess demand for labor compared to a market characterized by unemployment. Surprisingly though, this does not compromise market performance.
Keywords: D82; 330; Relational contracts; involuntary unemployment; Arbeitsvertrag; Implizite Kontrakte; Unfreiwillige Arbeitslosigkeit; Arbeitslosigkeit; Leistungsmotivation; Leistungskontrolle; Arbeitsnachfrage; Wettbewerb; Theorie